2021
DOI: 10.1016/j.kint.2021.02.023
|View full text |Cite
|
Sign up to set email alerts
|

A novel claudin-10 mutation with a unique mechanism in two unrelated families with HELIX syndrome

Abstract: HELIX syndrome, characterized by hypohidrosis, electrolyte imbalance, lacrimal gland dysfunction, ichthyosis, and xerostomia due to claudin-10 (CLDN10) mutations, was recognized in 2017. Here we describe two unrelated Saudi families with this syndrome due to a novel CLDN10 mutation with a unique mechanism of CLDN10 inactivation. The two consanguineous families include 12 affected individuals (three siblings in family 1 and nine members in family 2). They presented with hypokalemia and the abovementioned featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 27 publications
6
40
0
Order By: Relevance
“…However, this is only the sixth reported instance of a homozygous CLDN10 variant associated with human disease and the fourth such variant affecting both protein isoforms. 1 , 2 , 3 , 4 , 5 In conclusion, we demonstrated that claudin-10a/b G163A/G165A causes a variation of HELIX syndrome based on defective claudin-10 TJ strand assembly. Thereby, claudin-10b is more severely affected than claudin-10a.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, this is only the sixth reported instance of a homozygous CLDN10 variant associated with human disease and the fourth such variant affecting both protein isoforms. 1 , 2 , 3 , 4 , 5 In conclusion, we demonstrated that claudin-10a/b G163A/G165A causes a variation of HELIX syndrome based on defective claudin-10 TJ strand assembly. Thereby, claudin-10b is more severely affected than claudin-10a.…”
Section: Discussionmentioning
confidence: 57%
“…Of note, our data contrast with previous reports of xerostomia in HELIX patients. 2 , 3 , 4 , 5 , 28 However, quantitative assessment of saliva secretion has previously been performed solely by Hadj-Rabia et al 3 in three patients. Our dental findings indicate impaired enamel formation to be a novel phenotype of HELIX syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amelogenesis imperfecta is also frequently found in patients with genetic disorders related to kidney, skin and many other organs 14,24,28,29 and the autosomal recessive inheritance (OMIM 617671; Prevalence: <1 /1,000,000) [30][31][32][33][34][35] . In addition, it has been reported that the patients with HELIX syndrome displayed a very early and severe enamel wear 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Amelogenesis imperfecta is also frequently found in patients with genetic disorders related to kidney, skin, and other organs 16,26,30,31 . A disorder of this sort was recently found to be associated with loss‐of‐function variants of CLDN10 , resulting in the autosomal recessive HELIX syndrome characterized by hypohidrosis, electrolyte imbalance, lacrimal gland dysfunction, ichthyosis, and xerostomia (OMIM 617671; prevalence: <1/1,000,000) 32–37 . In addition, it has been reported that the patients with HELIX syndrome displayed a very early and severe enamel wear 34 .…”
Section: Introductionmentioning
confidence: 99%